Digital Technologies in Region Governance Practice - Z. A. Asalieva (Вестник Российского экономического университета имени Г. В. Плеханова)
Digital transformation of economy both on the macro-level and in view of regional and industry progressing forms one of national targets and aims at raising quality and comfort of life, development of business and competitive environment. The goal of the research is to identify key priorities and challenges of digital development of Russian economy on the regional level and digital opportunities of state governance. The article analyzes the use of digital technologies to manage national economy on the regional level. The author studied works by Russian and overseas researchers in the field of establishing information society, digital economy and digital state governance as the theoretical and methodological base of the research. The author provides materials of international expert and analytical organizations, the Global Economic Forum, the World Bank and national research institutions, the Higher Business School. The research gives an opportunity to find possibilities to implement the concept of e-government in order to improve the quality of state services, life comfort, development of business and competitive environment.